Comparative study for three protocols of general anesthesia in bucks: Raffal A. Omar; Omar Khalid Aziz; M. J. Eesa and Bilal Shaker Abed - Omar, Raffal A.; Eesa, M. J. (The Iraqi Journal of Veterinary Medicine, 2018)
The aim of this study was to evaluate three regimens in induction and maintenance of general anesthesia in local breed bucks and the investigation of the best protocol of them based on different parameters. Eighteen healthy adult bucks weighing (27.50 ± 0.682 kg), aged (1.989 ± 0.135 years) were used. Animals were divided randomly into three equal groups to undergo pre-experiment preparation. All groups were premedicated intravenously with (0.5 mg/ kg) Diazepam, ten min. Later, the induction for first group was done by Propofol (3 mg/kg B.W), second group was done by Ketamine Hcl (2 mg/kg B.W), while in the third group was done by Thiopental sodium (3mg/kg B.W). After intubation with suitable endotracheal tube, maintenance of the three groups was done by (1.3-1.5%) isoflurane and nitrous oxide with oxygen at ratio 2:1. All the three groups underwent the measurement of the following parameters; (Induction, recovery and duration times) Clinical parameters (heart rate, respiratory rate and body temperature); Clinical signs, analgesia, muscle relaxation; Liver enzyme (Aspartate Amino Transferase and Alanine Amino Transferase). The complete randomized design within statistical analysis system (SAS) program were used for statistical analysis as relevant with a significance level set at P<0.05. The results of this study showed that the induction of the anesthesia was smooth and uneventful in all the three groups and recovery time was shorter in 3rd group in comparison with 2nd and 1st groups. The three regimens showed no significant differences in heart rate. The 2nd group recorded a sharp decrease in respiratory rate and body temperature in comparison with 1st and 3rd groups. Analgesia was very suitable in all the three groups. There were significant changes among groups concerning Alanine Amino Transferase and, Aspartate Amino Transferase. It was concluded that all the three protocols were safe and caused no hazard effect on the animals.